2021
DOI: 10.1080/15548627.2021.1947730
|View full text |Cite
|
Sign up to set email alerts
|

A new flavor of cellular Atg8-family protein lipidation – alternative conjugation to phosphatidylserine during CASM

Abstract: Atg8-family protein lipidation is the most commonly used marker for monitoring autophagy. During macroautophagy, Atg8-family proteins are specifically conjugated to phosphatidylethanolamine (PE) in forming, double-membrane autophagosomes. A distinct, non-canonical autophagy pathway also operates, characterized by the Conjugation of ATG8s to endolysosomal Single Membranes (CASM). In our new study, we show that CASM is associated with the alternative conjugation of Atg8-family proteins to phosphatidylserine (PS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…In contrast to classical autophagy, the LAPasome is a single membrane vacuole. The term CASM (conjugation of ATG8 to single membranes) was introduced to describe these related pathways [80][81][82]. Detailed descriptions of the autophagy pathway have recently been published [66,83].…”
Section: A Brief Overview Of Autophagymentioning
confidence: 99%
“…In contrast to classical autophagy, the LAPasome is a single membrane vacuole. The term CASM (conjugation of ATG8 to single membranes) was introduced to describe these related pathways [80][81][82]. Detailed descriptions of the autophagy pathway have recently been published [66,83].…”
Section: A Brief Overview Of Autophagymentioning
confidence: 99%
“…Notably, unlike LAP, the observed LC3 conjugation to endocytic vacuoles is insensitive to antioxidants and is therefore unlikely to be induced by locally generated reactive oxygen species (ROS) (compare [ 71 ] and [ 9 ]). The LNCA in the acinar cells is probably a subtype of CASM; this conclusion is based on the common single-membrane LC3 conjugation for both processes and on the striking effect of V-ATPase inhibitors on LNCA [ 9 ] (the interaction of LC3-conjugating machinery with V-ATPases is a defining property of CASM [ 73 , 78 , 80 ]). Furthermore, both LNCA in the acinar cells and CASM require ATG16L1 with an intact C-terminal WD domain [ 9 , 75 , 76 ].…”
Section: Endocytic Vacuoles: Actination Rupture and Lap-like Non-cano...mentioning
confidence: 99%
“…However, within the framework of LAP, ATG8/LC3 conjugates to the single membrane of the phagosome (reviewed in [ 72 ]). Notably, in this case, ATG8/LC3 can bind to both phosphatidylethanolamine and phosphatidylserine [ 73 , 74 ]. Different domains of ATG16L are involved in LAP and canonical autophagy; the WD repeat-containing C-terminal domain (WD CT) of ATG16L1 is essential for LAP but dispensable for canonical autophagy [ 75 , 76 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the conjugation of the ATG8/LC3B family members to lipids, recently named "ATG8ylation" by analogy with ubiquitination, has been proposed to be a general mechanism involved in the maintenance of membrane homeostasis during remodeling (17,18). Interestingly, it has been shown that the conjugation of ATG8 proteins is not restricted to PE and that this protein can also be conjugated to phosphatidylserines (PS) (19,20). ATG8ylation involves an E1-like ATG7 protein, two E2-like ATG3 and ATG10 proteins and finally the E3-like complex ATG5−ATG12-ATG16L1.…”
Section: Introductionmentioning
confidence: 99%